'Extreme Mass Spectrometry': the role of mass spectrometry in the study of the Antarctic Environmentm. (November 2014) - Magi, E.; Tanwar, S.
<x xml:space="preserve">Abstract</x> The environment of Antarctica presents numerous challenges to life and exploration. Contained within its bleak landscape is a virtual storehouse of chemical and biological information that can provide clues about past conditions and events. Mass spectrometry is one of the best tools available for analyzing such a diverse sample set from an extreme environment. In the Special Feature, Emanuele Magi and Shivani Tanwar from the University of Genoa discuss the role of mass spectrometry in analyzing and understanding the many different facets of the Antarctic environment, from environmental contaminants to biomarkers and metabolism of organisms. (Cover Caption: Priestley Glacier, Antarctica, about 100 km long, originating at the edge of the polar plateau of Victoria Land, named for Raymond E. Priestley, geologist). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>